2005
DOI: 10.1007/bf03325859
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Cu, Zn and Ni from the wastewater by treated Nasturtium officinale

Abstract: Aquatic plants are well known in accumulating and in concentrating heavy metals. In this study, several physiological responses of aquatic vascular plant, Nasturtium officinale (watercress), which were elevated concentrations of copper, zinc and nickel have been investigated. It was found that Nasturtium officinale were able to accumulate both copper and zinc at upper levels, but was able to accumulate to nickel at low levels. The final goal of this work was to examine the copper, zinc and nickel uptake using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…The heavy metal emanating from effluents of various industries (such as tanneries, dye producers, textile dyeing plants, metal engineering, electroplating) may lead to the problem of heavy metal bioaccumulation in aquatic plants (Kara 2005) and fish (Hollis et al 2001;Long and Wang 2005;Marcussen et al 2007). It has been reported that heavy metals can accumulate in different tissues of freshwater fishes (Amundsen et al 1997;Ruangsomboon and Wongrat 2006) and marine fishes (Kalay et al 1999;Wong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The heavy metal emanating from effluents of various industries (such as tanneries, dye producers, textile dyeing plants, metal engineering, electroplating) may lead to the problem of heavy metal bioaccumulation in aquatic plants (Kara 2005) and fish (Hollis et al 2001;Long and Wang 2005;Marcussen et al 2007). It has been reported that heavy metals can accumulate in different tissues of freshwater fishes (Amundsen et al 1997;Ruangsomboon and Wongrat 2006) and marine fishes (Kalay et al 1999;Wong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic plants possess an immense potential to remove heavy metals from wastewater (Dushenkov et al, 1995;Kara, 2005). Though extensive literature is available highlighting the potential of several Salvinia species for accumulation/removal of various heavy metals including Ni, Cu, As, Pb, Cr, Zn from wastewaters (Sen and Mondal, 1990;Sen and Bhattacharya, 1994;Nigam et al, 1998;Nichols et al, 2000;Hoffman et al, 2004;Hadad et al, 2007), the physiological factors and regulatory mechanisms related to the greater potential of plants for tolerating high levels of heavy metals are not known.…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the aqueous solution is an important operational parameter in the adsorption process because it affects the solubility of the metal ions, concentration of the counter ions on the functional groups of the adsorbent and the degree of ionization of the adsorbate during reaction (Kaonga et al 2010;Ghazy and Ragab 2007;Kara 2005;Onundi et al 2010). In order to find optimal pH value for the sorption process, the removal of copper ions in the pH range 2-6 was investigated and the data are illustrated in the Fig.…”
Section: Effect Of Ph On Adsorptionmentioning
confidence: 99%